The development and application of a sub-channel code in ocean environment. (September 2016) - Wu, Pan; Shan, Jianqiang; Xiang, Xiong; Zhang, Bo; Gou, Junli; Zhang, Bin
Highlights: A sub-channel code named ATHAS/OE is developed for nuclear reactors in ocean environment. ATHAS/OE is verified by another modified sub-channel code based on COBRA-IV. ATHAS/OE is used to analyze thermal hydraulic of a typical SMR in heaving and rolling motion. Calculation results show that ocean condition affect the thermal hydraulic of a reactor significantly. Abstract: An upgraded version of ATHAS sub-channel code ATHAS/OE is developed for the investigation of the thermal hydraulic behavior of nuclear reactor core in ocean environment with consideration of heaving and rolling motion effect. The code is verified by another modified sub-channel code based on COBRA-IV and used to analyze the thermal hydraulic characteristics of a typical SMR under heaving and rolling motion condition. The calculation results show that the heaving and rolling motion affect the thermal hydraulic behavior of a reactor significantly.